Laboratory investigation of salt-water intrusion through porous media (2011)
" Flow rate of salt-water and fresh-water through porous media depends on the hydraulic gradient, porosity and hydraulic conductivity of the sand materials and the properties of the fluids such as density and viscosity. This study examined flow rate of salt-water and fresh-water in porous media in a modeled laboratory experiment. Porous materials were filled into the conduit of two arms glass cylindrical tube with valve (control) at the middle. Salt-water and fresh-water were made to flow through the porous materials from the different arms. The volume displacements of salt-water and fresh-water in the two arms glass cylindrical tube filled with riverbed sand of varying porosities were determined when the valve between the two arms was opened with different hydraulic heads of fluids in the tube. Salt-water displaced the fresh-water upward in the set up when hydraulic level of salt-water is greater than hydraulic level of fresh-water. Salt-water also displaced the fresh-water in the set up when the hydraulic level of salt-water is the same as the hydraulic fresh-water. But fresh-water displaced salt-water only when hydraulic level of fresh-water is greater than hydraulic level of salt-water. "